Mapping the risk landscape of childhood obesity: A narrative review of behavioral and socioeconomic determinants - Anwar Lubis; Slamet Widodo (Privietlab, 2025)
Childhood obesity is a critical global health concern with a rising prevalence in both developed and developing countries and is associated with substantial short- and long-term consequences, including metabolic, cardiovascular, and psychosocial disorders. This narrative review synthesizes recent evidence on the behavioral, familial, and socioeconomic determinants of childhood obesity to inform prevention strategies. Ten peer-reviewed articles published between 2015 and 2025 were reviewed, encompassing diverse populations from Asia, Europe, South America and Oceania. Studies met the inclusion criteria if they targeted children aged 2–18 years, defined overweight/obesity using standardized anthropometric measurements, and reported one or more risk factors. The extracted data were thematically analyzed into five domains: sociodemographic and family characteristics, dietary behaviors, physical activity and sedentary lifestyle, breastfeeding and early life exposures, and socioeconomic disparities. Across the included studies, unhealthy dietary patterns and insufficient physical activity were the most frequently cited modifiable risk factors, appearing in more than half of the studies. Maternal obesity, low parental education, and limited household income were consistently linked to higher obesity risk through both biological and environmental pathways, while short breastfeeding duration and cesarean delivery were recurrent early-life factors associated with increased prevalence. Socioeconomic disparities amplify exposure to obesogenic environments, particularly in disadvantaged communities. The findings indicate that childhood obesity is a multifactorial condition shaped by interdependent behavioral, familial, and structural determinants. Effective prevention requires equity-focused multisectoral strategies that integrate healthy eating promotion, physical activity encouragement, maternal and child health support, and interventions targeting the social determinants of health.